Competition or Liberation? Implications of Labour Automation in the Context of Cognitive Capitalism - Burgess, Russell (Carleton University, 2016)
Technologies in the first half of 21st century are developing new abilities to perform autonomously and compete with humans directly in more and more tasks, opening up the future possibility of increasing labour substitution. Using the theory of Cognitive Capitalism to examine advanced economies as the most recent form of capitalism shows that in the modern economy work is increasingly central to the lives of individuals due to new cognitive labour which requires more worker engagement than industrial labour. This requirement has strengthened the direct coercive mechanisms of the increasingly precarious wage relationship and weakened alternate income sources. This dissertation argues that automation in this context could be harmful to individuals required to depend on work to survive and evaluates three policy options against the goal of freeing individuals from this institutional constraint to work so that they can continue to fully and freely participate in society if widespread automation occurs.